Consumer passive legitimation in civil liability for risky and dangerous activities - Gianfelici, Mario Cesar (Universidad Nacional del Litoral, 2020)
The Art. 1757 CCCN does not define risky or dangerous activities. It only give us some guidelines to qualify them. This open concept needs doctrine and jurisprudence delimitation to avoid overflows. Risky and dangerous; have the same meaning. Is not required to use something to configure this cases of responsability. These activities included a set of actions, operations or works carried out by a company or organization, not an isolated event. It covers both intrinsically risky activities and those that become that by the means or circumstances in which them occurred. In order to classify an activity as risky or d angerous, the legal operator must be guided by statistical criteria, special controls requirement, the rules of experience or legal express characterization,such as electronically consuming contracts. Humans and legal persons are responsible for the damaged these activities caused when they do, use or obtain a profit from them, by themselves or by third parties, onerously or free of charge. It is also necessary that they can control or direct the tasks organization. It is expressly excluded liberal professionals. The executor and the consumer are not included. Disclaimers are the same that those of objective attribution factor.